Trypanosoma brucei multi-aminoacyl-tRNA synthetase complex formation limits promiscuous tRNA proofreading - Watkins, Rylan R.; Vradi, Anna; Shulgina, Irina; Musier-Forsyth, Karin (Frontiers in Microbiology, 2024)
Faithful mRNA decoding depends on the accuracy of aminoacyl-tRNA synthetases (ARSs). Aminoacyl-tRNA proofreading mechanisms have been well-described in bacteria, humans, and plants. However, our knowledge of translational fidelity in protozoans is limited. Trypanosoma brucei (Tb) is a eukaryotic, protozoan pathogen that causes Human African Trypanosomiasis, a fatal disease if untreated. Tb undergoes many physiological changes that are dictated by nutrient availability throughout its insect-mammal lifecycle. In the glucose-deprived insect vector, the tsetse fly, Tb use proline to make ATP via mitochondrial respiration. Alanine is one of the major byproducts of proline consumption. We hypothesize that the elevated alanine pool challenges Tb prolyl-tRNA synthetase (ProRS), an ARS known to misactivate alanine in all three domains of life, resulting in high levels of misaminoacylated Ala-tRNA Pro . Tb encodes two domains that are members of the INS superfamily of aminoacyl-tRNA deacylases. One homolog is appended to the N-terminus of Tb ProRS, and a second is the major domain of multi-aminoacyl-tRNA synthetase complex (MSC)-associated protein 3 (MCP3). Both ProRS and MCP3 are housed in the Tb MSC. Here, we purified Tb ProRS and MCP3 and observed robust Ala-tRNA Pro deacylation activity from both enzymes in vitro. Size-exclusion chromatography multi-angle light scattering used to probe the oligomerization state of MCP3 revealed that although its unique N-terminal extension confers homodimerization in the absence of tRNA, the protein binds to tRNA as a monomer. Kinetic assays showed MCP3 alone has relaxed tRNA specificity and promiscuously hydrolyzes cognate Ala-tRNA Ala ; this activity is significantly reduced in the presence of Tb alanyl-tRNA synthetase, also housed in the MSC. Taken together, our results provide insight into translational fidelity mechanisms in Tb and lay the foundation for exploring MSC-associated proteins as novel drug targets.